The ethics of occupational health and safety in Turkey: responsibility and consent to risk - Artvinli, Fatih (Acta Bioethica, 2016)
Work-related diseases, injuries, risks and deaths are the issues gaining importance especially in developing countries. The ethical dimensions of occupational health and safety issues have been relatively less examined. Responsibility, consent, autonomy, paternalism, choice and other concepts, such values or justifications used in medical ethics and bioethics are also applicable to occupational health and safety domain. This article examines the ethical issues of responsibility and consent to occupational risk. In this article, first, the concepts of consent and risk are defined, then different views on responsibility and consent to risk are discussed and finally responsibility of society and the government are examined.